Multidisciplinary Team Support for Psychological Aspect of Osteosarcoma Amputation in Children: A Case Report - Budi Kristianto; Yunias Setiawati (HM Publisher, 2021)
Introduction. Osteosarcoma is the most common primary bone tumor in children. The current management is the surgical method (amputation) and continued chemotherapy. When someone is expected to do this treatment, there will be various possible psychological reactions occur. This amputation condition will affect psychological symptoms both before and after the procedure. Case presentation. A girl, Ms. D, seven years old, first grade of elementary school, planned to be amputated with a diagnosis of right tibia proximal osteosarcoma. The patient is a child the second of 3 siblings. The patient was taken to Dr. Soetomo General Hospital, after checking at the hospital in Ponorogo, then a referral was given for further treatment. Patient is referred because the swelling in the right knee is getting bigger day by day. The patient is being treated and will be planned for surgery with a diagnosis of proximal osteosarcoma right tibia. The patient is consulted by a psychiatrist for assistance considering the patient will be carried out right leg amputation surgery. Conclusion.Chemotherapy with various side effects will also have an effect on the psychological condition of the patient. So there is a need for full involvement multidisciplinary in dealing with pediatric patients with osteosarcoma that will be carried out amputation to obtain optimal therapeutic results.